Optimization of aerobic fermentation of solid fertilizer from goat manure using response surface methodology (RSM) - Mandriana, Rizna Aini; Mafachir, Muhammad Tajul; Billah, Mu'tasim; Sari, Ni Ketut; Kurnianti, Ely; Suprihatin, Suprihatin (Universitas Lambung Mangkurat, 2026)
The increase in the goat population in Panceng District has resulted in an increase in the volume of goat waste which has the potential to pollute the environment if not managed properly. Goat manure has good nutrient content, but the high initial C/N ratio (30.47) indicates that the material is not yet stable and requires a fermentation process. This study aims to optimize the aerobic fermentation process using the Response Surface Methodology (RSM) with varying air flow rates (5–25 L/min) and oxidation times (16–24 days). The process was carried out in an in-vessel non-flow reactor with an active aeration system. Carbon content analysis using the Walkley–Black Modified Spectrophotometric method and nitrogen content analysis using the Kjeldahl Method and water content using the gravimetric method. The results showed that increasing the air flow rate and oxidation time caused a significant decrease in the C/N ratio from 30.47 to 11.52–17.62. The optimum conditions were obtained at an air flow rate of 20 L/min and an oxidation time of 22 days with a C/N ratio of 12.4769 and a water content of 23.3309%, and a desirability value of 1. These results show that optimization using RSM is able to produce solid organic fertilizer that meets SNI standards (<20).